Tahsin Learning Management for Blind Children through a Humanist, Inclusive, and Student-Centered Approach - Yulida Fauziah; Irawan Irawan; Syauqi Arinal Haqq (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
Learning tahsin for students with intellectual disabilities requires a specific instructional approach that accommodates their individual characteristics, abilities, and needs. This study aims to describe the application of humanistic, inclusive, and student-centered learning approaches in improving tahsin learning at PPSGRA Subang. A qualitative descriptive method is used, with data collected through observation, interviews, and documentation to obtain information related to teaching strategies, classroom atmosphere, and student learning progress. The results show that a humanistic approach creates a supportive learning environment that rewards students' efforts and improves their comfort in learning. An inclusive approach facilitates the adaptation of media, strategies, and learning activities so that each student can participate according to his or her abilities. Meanwhile, the student-centered approach increases active participation, motivation, and confidence in recognizing and reading the Arabic letters of the Qur'an. Overall, the integration of these three approaches effectively supports the improvement of tahsin abilities and the social-emotional development of students with intellectual disabilities.